Irrigação e sustentabilidade dos recursos solo e água na área do distrito de irrigação baixo Acaraú-Dibau-Ceará - Aquino, Deodato do Nascimento (2007)
Irrigation is an essential input that has enhanced, substantially, food production and has improved economic development in arid regions. Irrigation, also, has generated negative impacts to the environment and to human health. The aim of this work was to quantify and qualify the irrigation impacts and of the climatic seasonality over soil and water resource in Irrigated District of Baixo Acaraú, Ceará, Brazil. Ten points spread out over the studied area were selected as monitoring stations. Two of them were sited in irrigated fields. Samples were collected monthly from Dezember/2003 to November/2005, November/2006, March and May/2007. The samples were analyzed for: pH, electrical conductivity (EC), Ca2+, Mg2+, Na+, K+, HCO3 -, PO4 -2, Cl-, NH4 +, NO3 -, SO4 -2 and Sodium Adsorption Ratio (SAR). Soil samples were collected in two different types of land use: irrigated field and uncultivated area field. Soils samples were taken for each 50 cm until water table (7 m) was reached, during wet and irrigation seasons. Multivariate statistical method, cluster analysis, was applied to classify the shallow wells inte similar groups in relation to water quality. To identify spacial variability of Na+, Cl-, CE, PO4 -2 e NO3 - in the water table it was used a GIS platform and the software: Global Mapper 5.0, ArcGis 9.1. The geostatistic process was performed using the Surfer 7.0. According to the results the highest values of changeable bases (Ca2+, Mg2+, Na+ e K+), Cl-, SAR AND NO3 - were presented in the water of P1 (sample station 1). These values were over the acceptable limit of Class 1 defined by CONAMA (Resolution 357/05). The analyzed variables showed a high spacial variability and a low temporal variability. The used soil management in the irrigated field, where shallow wells (P3 and P4) were sited, is not contributing to the contamination or water table by salts, yet. Also, the results show have that irrigation caused the groundwater concentration of NO3–N to increase from 1.52 to 19.3 mg L-1, thereby, exceeding the standards of the World Health Organization (WHO).